Remote Leadership in Higher Education/Public Sector: A Comparative Bibliometric Analysis of the Global South vs. the Global North - Loso Judijanto (Westscience Press, 2025)
The rapid expansion of remote and hybrid work arrangements has positioned remote leadership as a critical concern for higher education institutions and public-sector organizations worldwide. This study aims to map and compare the global research landscape on remote leadership by conducting a comparative bibliometric analysis between the Global South and the Global North. Using data retrieved from the Scopus database and analyzed with VOSviewer, the study examines publication trends, co-authorship networks, citation structures, and thematic evolution within the field. The findings indicate that remote leadership has emerged as a central and integrative concept, closely linked to e-leadership, virtual teams, and established leadership theories such as transformational and authentic leadership. More recent research increasingly emphasizes relational and human-centered themes, including communication, trust, and employee outcomes, particularly in higher education contexts. The analysis also reveals a strong concentration of knowledge production and collaboration networks in the Global North, while contributions from the Global South remain limited and contextually constrained by digital infrastructure and institutional capacity. Overall, this study provides a systematic overview of the intellectual structure and developmental trajectory of remote leadership research and highlights the need for more inclusive, context-sensitive, and regionally grounded scholarship to advance leadership theory and practice in digitally mediated public and educational organizations.